Clinical utility of arterial spin labeling for preoperative grading of glioma. Issue 4 (31st August 2018) - Fu, Jun; Li, Linchen; Wang, Xinjun; Zhang, Min; Zhang, Yan; Li, Zhanzhan
Abstract : There were obvious differences in biological behavior and prognosis between low- and high-grade gliomas, it is of great importance for clinicians to make a right judgement for preoperative grading. We conducted a comprehensive meta-analysis to evaluate the clinical utility of arterial spin labeling for preoperative grading. We searched the PubMed, Embase, China National Knowledge Infrastructure, and Weipu electronic databases for articles published through 10 November 2017 and used 'arterial spin-labeling' or 'ASL perfusion, grading' or 'differentiation, glioma' or 'glial tumor, diagnostic test' as the search terms. A manual search of relevant original and review articles was performed to identify additional studies. The meta-analysis included nine studies. No obvious heterogeneity was found in the data in a fixed-effect model. The pooled sensitivity and specificity were 90% (95% confidence interval (CI): 0.84–0.94) and 91% (95% CI: 0.83–0.96), respectively, and the pooled positive likelihood ratio (PLR) and negative likelihood ratio (NLR) were 10.40 (95% CI: 2.21–20.77) and 0.11 (95% CI: 0.07–0.18). The diagnostic odds ratio (DOR) was 92.47 (95% CI: 39.61–215.92). The diagnostic score was 4.53 (95% CI: 3.68–5.38). The area under the curve (AUC) was 0.94 (95% CI: 0.91–0.96). Subgroup analyses did not change the pooled results. No publication bias was found ( P =0.102). The normalized maximal tumor blood flow/normal white matter ratio obtained with the arterial spin labeling technique was relatively accurate for distinguishing high/low-grade glioma. As a non-invasive procedure with favorable repeatability, this index may be useful for clinical diagnostics.